Explainable Artificial Intelligence in Stroke from the Clinical, Rehabilitation and Nursing Perspectives - Jia, Jie; Hu, Yan; Zhang, Dingguo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
As we know, strokes are one of the world's leading causes of death, and the cruel aspect of a stroke is that it leaves people with severe functional disability and/or cognitive impairment. Strokes have a significant impact on economies worldwide, as it is estimated that about 10% of the male population and 8% of the female population are affected by them. Such people need personal help in their everyday life and must be materially supported by social services. With the advancement of medicine, artificial intelligence, and new technologies have been developing rapidly and are gradually applied in diseases of the nervous system, increasingly helping diagnosis, treatment, rehabilitation, and prognosis of disease.This Special Issue has collected the 14 papers on artificial intelligence and new technologies in strokes, including in the aspects of diagnosis, treatment, prognosis, rehabilitation, and nursing. We welcome your reading.